The association between polymorphism XRCC1 (rs25487) and the susceptibility of chemical industry workers to benzene - Negar Musavi; Farzaneh Tafvizi; Yaser Mansoori (Journal of Advanced Biomedical Sciences, 2018)
Background & Objective: Benzene, as a carcinogenic compound, can damage DNA by producing free oxygen radicals. Benzene effects have been reported in the blood system. It seems that XRCC1 gene, as a gene involved in the repair of damaged bases, plays a role in the sensitivity of individuals to benzene. The purpose of this study was to investigate the association between rs25487 polymorphism in XRCC1 gene and the susceptibility of chemical industry workers against benzene. Material & Methods: In this case-control study, 60 cases and 60 controls who were exposed to benzene for 2 consecutive years were examined. People who did not have any changes in blood parameters were selected as the control group and those who have shown lymphocytes outside the normal range were considered as a case group. Blood samples were collected from chemical workers. Gene polymorphism was determined by RFLP-PCR using MSP1enzym. Results: There was no significant difference between allelic frequencies A and G (P >0.05). No significant association was found between XRCC1 polymorphism and benzene susceptibility and lymphocytic abnormalities (OR: 1.43, 95% CI (0.47 - 4.31), P = 0.52). Conclusion: It seems that rs25487 polymorphism in the XRCC1 gene does not play a role in the sensitivity of individuals to benzene. Of course, due to the role of XRCC1 gene in response to DNA damage, other polymorphisms of this gene and polymorphism that are targeted in this study are evaluated at a wider level.